HUBUNGAN ANTARA PENGETAHUAN, SIKAP, DAN PERILAKU PASIEN TERHADAP PENGGUNAAN OBAT BERLABEL HALAL DI APOTEK MERDEKA - Fatiha, Chilmia Nurul; Nabilah Maya Maharani (Nusantara Hasana Journal, 2024)
Indonesia is a country that has the largest Muslim population in the world which of course has an interest in the distribution of products that are safe and have halal standards. Because Muslims automatically become the biggest consumers in this country as well as being the target and target for imports from other countries. The aim of this research is to determine the relationship between patient knowledge, attitudes and behavior towards the use of medicines labeled halal. This research uses a cross-sectional research method with observation methods. This sampling technique uses a purposive sampling technique. The results of the research on the relationship between the level of knowledge and the use of halal labeled drugs have a Sig-2 tailed value of 0.05 <=0.05 and the relationship between attitudes towards the use of halal labeled drugs has a Sig-2 tailed value of 0.01 <0.05 and the relationship between behavior and use. drugs labeled halal have a Sig-2 tailed value of 0.01 < 0.05 so there is a significant relationship between the variables of knowledge, attitude and patient behavior towards the use of drugs labeled halal at the Merdeka Pharmacy.